Kinematic Analysis of Heating Ventilating and Cooling Module Parts of Automobile Air Conditioning System Using CAE Tools - Singh, Baljeet (My University, 2011)
With the automotive air-conditioning industry aiming at higher levels of quality, cost effectiveness and a short time to market, the need for simulation is at an all time high. In the present work, the use of multibody dynamics approach is proposed in the simulation and analysis of the airflow control mechanisms of an automotive HVAC module for opening various doors/dampers used for passenger comfort. The movements of various parts have been kinematically analyzed. A new method for cam design has been developed which is faster and simpler than the existing method. Two HVAC kinematic mechanism are designed, one with single link configuration and other with two link configuration for the same output. The single lever configuration leads to higher torque requirement along with more space requirement. Torque required in the two link configuration is lesser than in the existing design, thus lowering the effort required to rotate the cam from the control panel.
M.E. (CAD/CAM and Robotics)
Keywords: MBD; HVAC Kinematicsulation; SIMULATION